The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.ejcts.2004.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations and late adverse outcome in Marfan patients following cardiovascular surgery☆

Abstract: The incidence of reoperations is significantly higher in patients who presented initially with acute type A aortic dissection than in those with dilatation only. In addition, this survey demonstrates that unexpected fatal outcome may appear in the remaining native aorta following uncomplicated elective aortic root surgery, even if the aorta is normal-sized. A close follow-up of all Marfan patients is necessary to detect asymptomatic changes requiring surgery because complex elective redo-operations can be perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Regarding distal aortic dissection in patients with MFS, Carrel et al reported that 14 of 71 (20.5%) patients with MFS who had undergone surgery for annulo-aortic ectasia subsequently underwent a total of 27 aortic reoperations during a mean follow-up period of 5.2 years. 12 More importantly, initial aortic root surgery was performed for AAAD in 13 of the 14 patients. The long-term outcome of aortic root replacement in MFS patients differs between those who undergo surgery for aortic dissection and those without dissection because patients with MFS tend to require multi- ple surgical interventions if chronic dissection remains in the native distal aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding distal aortic dissection in patients with MFS, Carrel et al reported that 14 of 71 (20.5%) patients with MFS who had undergone surgery for annulo-aortic ectasia subsequently underwent a total of 27 aortic reoperations during a mean follow-up period of 5.2 years. 12 More importantly, initial aortic root surgery was performed for AAAD in 13 of the 14 patients. The long-term outcome of aortic root replacement in MFS patients differs between those who undergo surgery for aortic dissection and those without dissection because patients with MFS tend to require multi- ple surgical interventions if chronic dissection remains in the native distal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…6 Aortic dissection in this subgroup is most often related to an underlying connective tissue disease, such as Marfan syndrome (MFS); 6,7 however, some younger patients do not have any underlying connective tissue disease. Clinical outcomes among patients with MFS and acute type A aortic dissection (AAAD) are generally known, [8][9][10][11][12] but there are few reports based solely on age rather than etiology that describe patient characteristics and treatment outcomes among young patients with AAAD.…”
mentioning
confidence: 99%
“…However, following proximal aortic surgery, particularly in the presence of chronic dissection, the risk of aneurysmal dilatation of the distal aorta is substantial. Distal aortic complications are a primary cause of late death following root surgery [3,7], and 5-35% of MFS patients require further surgery depending upon the extent of previous surgery and the rigor of follow-up [8,19]. Risk factors for late reoperations are acute or chronic dissection at the time of initial surgery, aneurysms involving major peripheral arteries, hypertension and a smoking history [20].…”
Section: Discussionmentioning
confidence: 99%
“…1). While there is abundant literature regarding proximal aortic procedures in MFS, there are little data on the progression and management of distal aortic complications [4,5,[8][9][10]. In this study, we report a consecutive series of MFS patients with distal dissection.…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, many patients need second operations for aneurysms or dissections distal from the aortic root (figure 3). 8,9 In fact, the Marfan syndrome may affect any vessel in which elastin fibres are an important structural component of its wall. This applies to the entire aorta, although elastin is found in diminishing quantities from its proximal to its distal part.…”
mentioning
confidence: 99%